2020
DOI: 10.1371/journal.pone.0231128
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pollution characteristics of antibiotic resistant genes in one high anthropogenically-impacted river

Abstract: The objectives of this study were to comprehensively investigate the occurrence, distribution, and mobility of antibiotic resistant genes (ARGs) in the biofilm, water, and sediment from a section of the Weihe-river, in the northern Henan province, China. The abundances of nine ARGs belonging to four commonly used antibiotic classes (tetracyclines, sulfonamides, fluoroquinolones, and multidrug) and class 1 integron-integrase gene (intI1) were quantified. Sulfonamides gene (sulI) accounted for the highest percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…In a recent study on the three rivers in Nepal (the Sundarijal, Thapathali, and Chovar Rivers), the abundance levels of the intI1 gene were measured in the range of 15-5 × 10 6 copies/mL, which is slightly lower than that in the Saigon River in Ho Chi Minh City [37]. The level of the intI1 gene was observed to associate with the abundance of ARG over time in anthropogenically-impacted rivers and to significantly correlate with human pathogens in a wastewater treatment plant [14,60,63,64]. The high abundance of three integrons (intI1, intI2, and intI3), and the target ARG genes found in the Saigon River impacted by various human activities likely indicates potential widespread antibiotic resistance across the bacterial community in the aquatic environment via horizontal gene transfer.…”
Section: Occurrences Of Args and Integrons In The Saigon Rivermentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study on the three rivers in Nepal (the Sundarijal, Thapathali, and Chovar Rivers), the abundance levels of the intI1 gene were measured in the range of 15-5 × 10 6 copies/mL, which is slightly lower than that in the Saigon River in Ho Chi Minh City [37]. The level of the intI1 gene was observed to associate with the abundance of ARG over time in anthropogenically-impacted rivers and to significantly correlate with human pathogens in a wastewater treatment plant [14,60,63,64]. The high abundance of three integrons (intI1, intI2, and intI3), and the target ARG genes found in the Saigon River impacted by various human activities likely indicates potential widespread antibiotic resistance across the bacterial community in the aquatic environment via horizontal gene transfer.…”
Section: Occurrences Of Args and Integrons In The Saigon Rivermentioning
confidence: 95%
“…Efflux pumps are transport proteins capable of moving toxic substances (e.g., antibiotics and heavy metals) out of the bacterial cells and they play a major role in both intrinsic and acquired multidrug resistance [58,59]. In a recent study, Wei Hou et al reported a high abundance and diversity of genes encoding efflux pumps in nine lake and reservoirs in the north of China and suggested that efflux pumps are likely a predominant resistance mechanism in natural water bodies [60]. In this study, the occurrence of the efflux pump gene oqxB in the surface water was found to range from 53 to 4.6 × 10 5 copies/mL (Figure 1, Table S3).…”
Section: Occurrences Of Args and Integrons In The Saigon Rivermentioning
confidence: 99%
“…Some previous works had already pointed out the presence of pharmaceuticals (including AZM, CPR, CLR, LVX, NFX, SMX and TMP) (Aubertheau et al, 2017;Auguet et al, 2017;Carles et al, 2021;Valdés et al, 2021) and MGEs (integrons) in similar samples (Aubertheau et al, 2017;Auguet et al, 2017;Chen et al, 2020;Li and Zhang, 2020). However, it was not clear how the presence of integrons can be linked to the presence of ATBs, as integrons also contain genes other than ARGs or encoding proteins of unknown function.…”
Section: What Potential Risk Does River Biofilm Contamination Pose?mentioning
confidence: 99%
“…Гени резистентності не лише залишаються в різних природних матрицях, але й мігрують, трансформуються, поширюються і дифундують в інші біотопи навколишнього середовища. І, як результат, вони дестабілізують навколишнє середовище, потрапляють в харчовий ланцюг, впливають на здоров'я людини (Li, Zhang, 2020). Тому інформаційно-просвітницька робота, проведення моніторингу антибіотикорезистентної мікробіоти у ґрунтовій та водній екосистемах є життєво важливими заходами, що спрямовані на обмеження поширення забруднення навколишнього середовища та збереження біорізноманітності, екосистеми та здоров'я людини.…”
Section: висновкиunclassified